Middle East - Morrison, Ian A. (Madison, NJ : Steck-Vaughn Co., 1991)
A general survey of the Middle East with information on its geography, languages, religions, history, occupations, family life, cities, education, food, and legacies.
Includes index.
Booklist
Voice of Youth Advocates
5-8
Keywords: Middle East -- Juvenile literature; Middle East; Middle East